Use of Picture Media to Improve the Descriptive Writing Skills of Grade III Students of SD Ketapang Indah - Safinah; Jarmini (Journal of Media and Learning Technology, 2025)
This study aims to improve the descriptive writing skills of third-grade students at the UPTD SPF (Student Learning Implementation Unit) of Ketapang Indah Public Elementary School through the use of images. The background of this study was the low level of students' descriptive writing skills, as indicated by preliminary results: only 35% of 28 students achieved the Minimum Completion Criteria (KKM) of 70, with an average score of 63.5. This study used the Classroom Action Research (CAR) method, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection instruments included writing tests, observations of student activities, and documentation. The results showed a significant improvement in students' descriptive writing skills after the application of images. In cycle I, the average student score increased to 71.8, with a completion percentage of 67.8%. Further improvement occurred in cycle II, with an average score of 82.3 and a learning completion rate of 89.2%. Furthermore, observations showed that students were more active, enthusiastic, and motivated when writing descriptions using images. Thus, the use of images has proven effective in improving the descriptive writing skills of third-grade students. This medium can be used as a creative, engaging learning alternative that aligns with the developmental characteristics of elementary school students.